The Decline of Deep Brain Stimulation for Obsessive–Compulsive Disorder Following FDA Humanitarian Device Exemption Approval - Pinckard-Dover, Heather; Ward, Herbert; Foote, Kelly D. (Frontiers in Surgery, 2021)
Background: In February 2009, the US Food and Drug Administration (FDA) granted Humanitarian Device Exemption (HDE) for deep brain stimulation (DBS) in the anterior limb of the internal capsule (ALIC) for the treatment of severely debilitating, treatment refractory obsessive–compulsive disorder (OCD). Despite its promise as a life altering treatment for patients with otherwise refractory, severely debilitating OCD, the use of DBS for the treatment of OCD has diminished since the FDA HDE endorsement and is now rarely performed even at busy referral centers. We sought to identify factors hindering OCD patients from receiving DBS therapy. Materials and Methods: University of Florida (UF) clinical research databases were queried to identify patients evaluated as potential candidates for OCD DBS from January 1, 2002 to July 30, 2020. A retrospective review of these patients' medical records was performed to obtain demographic information, data related to their OCD, and details relevant to payment such as third-party payer, study participation, evaluation prior to or after HDE approval, and any stated factors prohibiting surgical intervention. Results: Out of 25 patients with severe OCD identified as candidates for DBS surgery during the past 18 years, 15 underwent surgery. Prior to FDA HDE approval, 6 out of 7 identified candidates were treated. After the HDE, only 9 out of 18 identified candidates were treated. Seven of the 9 were funded by Medicare, 1 paid out of pocket, and 1 had “pre-authorization” from her private insurer who ultimately refused to pay after the procedure. Among the 10 identified OCD DBS candidates who were ultimately not treated, 7 patients—all with private health insurance—were approved for surgery by the interdisciplinary team but were unable to proceed with surgery due to lack of insurance coverage, 1 decided against surgical intervention, 1 was excluded due to medical comorbidities and excessive perceived surgical risk, and no clear reason was identified for 1 patient evaluated in 2004 during our initial NIH OCD DBS trial. Conclusion: Based on compelling evidence that DBS provides substantial improvement of OCD symptoms and markedly improved functional capacity in 2 out of 3 patients with severely debilitating, treatment refractory OCD, the FDA approved this procedure under a Humanitarian Device Exemption in 2009, offering new hope to this unfortunate patient population. A careful review of our experience with OCD DBS at the University of Florida shows that since the HDE approval, only 50% of the severe OCD patients (9 of 18) identified as candidates for this potentially life altering treatment have been able to access the therapy. We found the most common limiting factor to be failure of private insurance policies to cover DBS for OCD, despite readily covering DBS for Parkinson's disease, essential tremor, and even dystonia—another HDE approved indication for DBS. We have identified an inherent discrimination in the US healthcare system against patients with medication-refractory OCD who are economically challenged and do not qualify for Medicare. We urge policy makers, insurance companies, and hospital administrations to recognize this health care disparity and seek to rectify it.